Horthy Miklós, a tengerész : az első világháborús évek, 1914-1918 - Nagy, Miklós Mihály (Közép-Európai Közlemények, 2013)
One of the significant personalities of 20th century Hungarian history is the admiral Miklós Horthy, who was the head of state during the decades between the two world wars and during World War II. In Hungarian historical awareness, he is primarily regarded as a governor. What is less known is that in his early career – for three and a half decades – he served in the navy of the Austro-Hungarian Monarchy, and finished his naval career as the last commander-in-chief of this organization. He was considered the most important naval commander in Hungarian military history, whose engagements during World War I are mentioned in works of universal military history. His years spent with the navy, along with his fame as a naval officer, his military upbringing and service in the navy all shaped his mentality and conduct as head of state. He remained a naval commander even as the country’s governor. Being an admiral defined his authority as head of state as the country was governed by a person who had significant military accomplishments, was practiced in domestic and foreign policy, and was well-travelled. Therefore, in Miklós Horthy’s case, it is impossible to separate his decades spent as governor from the years of World War I and the period preceding it. The present study discusses this tight relationship while providing an overview of Miklós Horthy’s accomplishments as commander in chief and describes their impact on his image as governor.